ความผูกพันของพนักงานต่อบริษัท พรีเซิร์ฟ ฟู้ด สเปเชียลตี้ จำกัด - ชัยวัฒน์ เหล่าสันติสุข (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to study the level of and the factors that affected employee engagement at Preserved Food Specialty Co. Ltd. The samples were the company’s 272 employees. The researcher used the 4 concepts of employee engagement which consisted of company, job, human resource management, and leadership. The data used for the analysis was primary data collected from self-administered questionnaire. The data was then analysed by frequency, percentage, mean, T-test, ANOVA and Linear Regression. The results of the study showed that most questionnaire respondents were female (58.8%), 26-35 years old (46.7%), single (51.5%), with education of lower than high school (33.5%). They had been working at the company for 1-5 years (40.8%) and most were operational employees (96.3%). The results showed that the employees at Preserved Food Specialty Co. Ltd. were ranked at the “engaged” level. They ranked leadership, organisation, job, and human resource management, respectively, at the high level. The factors that affected employee engagement positively and showed statistic significance were human resource management and leadership, respectively. However, personal factors namely gender, age, marital status, education, work period, job, and position did not statistically relate to the overall level of employee engagement.